Strukturnaja model' samorealizacii sportsmena v uslovijach professionalizacii v dzjudo - Bagadirova, S. K. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
Exercising provides a person with great opportunities for self-realization. In this regard, knowledge of the features of self-realization in sports will allow predicting the effects of self-realization in conditions of professionalization in sports. The purpose of this work was to review and formulate a structural model of the athlete`s self-realization in the conditions of professionalization in judo. In the model, we have identified the following structural components: motivation-target; informative; appraising and effective. The factors and conditions that determine self-realization are described. The analysis of the types of self-realization is carried out: basic, esoteric (internal) and exoteric (external) self-realization (according to V.V. Bailuk). The characteristic is given to the levels of self-realization (adaptive, reproductive, productive) and the criteria for assessing self-realization in sports (productive (objective and social) and personal (subjective and personal)). In the model, we have shown the interdependence of professionalization and self-realization, as well as the influence on these processes and the result of conditions such as human potential, judo requirements, judo resources.